Novel biomedical applications of Cerenkov radiation and radioluminescence imaging. Issue 2 (March 2015) - Spinelli, Antonello E.; Boschi, Federico
Abstract: The main goals of this review is to provide an up-to-date account of the different uses of Cerenkov radiation (CR) and radioluminescence imaging for pre-clinical small animal imaging. We will focus on new emerging applications such as the use of Cerenkov imaging for monitoring radionuclide and external radiotherapy in humans. Another novel application that will be described is the monitoring of radiochemical synthesis using microfluidic chips. Several pre-clinical aspects of CR will be discussed such as the development of 3D reconstruction methods for Cerenkov images and the use of CR as excitation source for nanoparticles or for endoscopic imaging. We will also include a discussion on radioluminescence imaging that is a more general method than Cerenkov imaging for the detection using optical methods of alpha and gamma emitters. Highlights: Small animal Cerenkov luminescence imaging. Cerenkov luminescence tomography. Radioluminescence imaging. Human Cerenkov imaging.